Sistem Informasi Pengelolaan Surat Masuk dan Nomor Surat Keluar Berbasis WEB Studi Kasus Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Ngawi - Nur Setya, Ichwan; Fatim Nugrahanti; Andi Rahman Putera (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
The mail management system is a much-needed development in the current era of information technology development, especially in an agency. However, at the Tourism, Youth and Sports Office of Ngawi Regency, the management of correspondence which can manage incoming mail and outgoing mail numbers is still done manually, namely by recording it in a large book because it collects data every year.The problem that occurs is the difficulty in finding recorded data, which must be searched manually in a book with the risk that the book will be damaged due to search activity. Furthermore, when making outgoing letter numbers, there is also a problem when you need a letter number on a date that has already passed.This research was carried out by using the extreme programming method which is a derivative of the Agile method which uses an object-oriented approach. The stages involved in the extreme programming method are Planning, Design, Coding, and Testing. The results of this study are Information System for Management of Incoming Mail and Outgoing Mail Numbers Web-Based at the Tourism, Youth and Sports Office of Ngawi Regency.